2019
DOI: 10.1038/s41569-019-0305-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mitral valve regurgitation by cardiovascular magnetic resonance imaging

Abstract: | Mitral regurgitation (MR) is a common valvular heart disease and is the second most frequent indication for heart valve surgery in Western countries. Echocardiography is the recommended first-line test for the assessment of valvular heart disease, but cardiovascular magnetic resonance imaging (CMR) provides complementary information, especially for assessing MR severity and to plan the timing of intervention. As new CMR techniques for the assessment of MR have arisen, standardizing CMR protocols for research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 71 publications
2
116
0
1
Order By: Relevance
“…Multiple CMR techniques are used in order to get a detailed description of the condition and a reliable conclusion. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple CMR techniques are used in order to get a detailed description of the condition and a reliable conclusion. 9 …”
Section: Discussionmentioning
confidence: 99%
“…CMR studies have shown that stroke volume (SV) determined in the ascending aorta with 2D PC flow in healthy controls decrease the more distally in the ascending aorta the measurement is performed, 4 5 and the phenomenon is even more pronounced under pathological conditions. 5–8 While a recent consensus statement recommends measuring forward aortic volume at the level of the sinotubular (ST) junction, 9 different measurement locations in the aorta are regularly used ( table 1 ). In some studies, measurements from different locations are used indiscriminately, 10 and some studies do not report the location of flow measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Two techniques are employed for MR quantification by CMR: SSFP imaging for LV forward volume and phase contrast imaging for LV forward volume. Unlike echocardiography, which requires the integration of multiple parameters in assessing MR severity, CMR relies on quantitative parameters, mainly RVol and RF [12,20].…”
Section: Cmr In Assessing Chronic Mrmentioning
confidence: 99%
“…19,26,27 Cardiovascular magnetic resonance imaging Cardiovascular magnetic resonance imaging is clinically useful in the assessment of MR in terms of identification of mechanisms, quantification of severity, and determination of its cardiac consequences on cardiac chamber remodeling. 28 Cardiovascular magnetic resonance imaging is indicated when echocardiography is not adequate to assess MR severity, LV and right ventricular volumes, and systolic function. The advantage of cardiovascular magnetic resonance imaging in revealing the presence, location, and degree of myocardial scar or replacement fibrosis in the atria may play a role in the overall assessment of AFMR.…”
Section: Echocardiographymentioning
confidence: 99%